The prion protein constitutively controls neuronal store-operated Ca2+ entry through Fyn kinase - De Mario, Agnese; Castellani, Angela; Peggion, Caterina; Massimino, Maria Lina; Lim, Dmitry; Hill, Andrew F.; Sorgato, M. Catia; Bertoli, Alessandro (Frontiers in Cellular Neuroscience, 2015)
The prion protein (PrPC) is a cell surface glycoprotein mainly expressed in neurons, whose misfolded isoforms generate the prion responsible for incurable neurodegenerative disorders. Whereas PrPC involvement in prion propagation is well established, PrPC physiological function is still enigmatic despite suggestions that it could act in cell signal transduction by modulating phosphorylation cascades and Ca2+ homeostasis. Because PrPC binds neurotoxic protein aggregates with high-affinity, it has also been proposed that PrPC acts as receptor for amyloid-β (Aβ) oligomers associated with Alzheimer’s disease (AD), and that PrPC-Aβ binding mediates AD-related synaptic dysfunctions following activation of the tyrosine kinase Fyn. Here, use of gene-encoded Ca2+ probes targeting different cell domains in primary cerebellar granule neurons expressing, or not, PrPC allowed us to investigate whether PrPC regulates store-operated Ca2+ entry (SOCE) and the implication of Fyn in this control. Our findings show that PrPC attenuates SOCE, and Ca2+ accumulation in the cytosol and mitochondria, by constitutively restraining Fyn activation and tyrosine phosphorylation of STIM1, a key molecular component of SOCE. This data establishes the existence of a PrPC-Fyn-SOCE triad in neurons. We also demonstrate that treating cerebellar granule and cortical neurons with soluble Aβ(1-42) oligomers abrogates the control of PrPC over Fyn and SOCE, suggesting a PrPC-dependent mechanism for Aβ-induced neuronal Ca2+ dyshomeostasis.